Intervención cognitiva conductual y dialéctica conductual en la conducta suicida - Duval Cabrera, María Teresa (My University, 2019)
In terms of mental health, crises don’t necessarily refer to traumatizing situations or events, but to the reaction of the individual. A person may feel deeply affected while another little or nothing has adverse effects, which is why it is thought appropriate to recognize the factor that triggered the crisis causing vulnerability that exceeds the current resources of the individual and the previous coping strategies. When it’s not possible to assimilate, adapt, start new forms of coping and control of emotions, it could have a greater deterioration and the development of destructive behaviors, including suicidal behavior. Suicidal behavior is one of the main causes of injuries and deaths around the world, is a complex and multifactorial phenomenon, is formed by suicidal ideas, self-harm, suicidal crisis, suicide attempt and suicide; however the early detection of risk factors involved will allow us to address this problem under a meticulous process. It is known that it can be originate in response to a daily life crisis and to psychopathological crises, determining the therapeutic approach. Evidence-based interventions include procedures designed to directly attack suicidal risk. Interventions that have demonstrated greater efficacy according to several systematic reviews have been all those of cognitive behavioral tendency, including dialectical behavioral therapy, problem solving and mindfulness, because they have helped significantly to the reduction of thoughts, hopelessness and suicidal behavior in addition the gains made have often been maintained over time.
En términos de salud mental, las crisis no necesariamente se refieren a situaciones o eventos traumatizantes, sino a la reacción del individuo. Una persona puede sentirse profundamente afectada mientras que otra poco o nada presenta efectos adversos, es por ello que se cree pertinente reconocer el factor que desencadenó la crisis provocando vulnerabilidad que excede los recursos actuales del individuo y las estrategias previas de afrontamiento. Cuando no se puede asimilar, adaptar, poner en marcha nuevas formas de afrontamiento y control de emociones podría llegar a presentar un mayor deterioro y el desarrollo de conductas destructivas, entre ellas la conducta suicida. La conducta suicida es una de las principales causas de lesiones y muertes alrededor de todo el mundo, es un fenómeno complejo y multifactorial, conformada por ideas suicidas, autodaño, crisis suicida, intento autolítico y suicidio; sin embargo la detección temprana de factores de riesgo y protección implicados permitirán abordar este problema bajo un meticuloso proceso. Se conoce que puede originarse en respuesta a una crisis de la vida cotidiana y a crisis psicopatológicas determinando el abordaje terapéutico. Las intervenciones basadas en evidencias incluyen procedimientos diseñados para atacar directamente el riesgo suicida. Las intervenciones que han demostrado mayor eficacia según varias revisiones sistemáticas han sido todas aquellas de tendencia cognitivo conductual, entre ellas terapia dialéctico conductual, de resolución de problemas y mindfulness, debido a que han ayudado significativamente a la reducción de pensamientos, desesperanza y la conducta suicida además las ganancias realizadas a menudo se han mantenido con el tiempo.
Keywords: CONDUCTA SUICIDA; CRISIS; CONDUCTUAL; INTERVENCION COGNITIVA